Cd(II), Ni(II), and Co(II) complexes based on a pyridyl–amine Schiff-base ligand: [M(L)2(NO3)]·(NO3) (M = Cd, Ni, Co), cis-[CoL2Cl2]·(C6H6), and [Co(L)3]·(ClO4)2 (CH3CN)2 (H2O) (L = N-(2-pyridylmethylene)benzene-1, 4-diamine, (2-py)CHNC6H4NH2). (1st February 2019) - Lee, Sung Jin; Lee, Soon W.
Graphical abstract: A pyridyl–amine Schiff-base compound (L = N -(2-pyridylmethylene)benzene-1, 4-diamine) reacted with several metal salts to give molecular complexes: [M(L)2 (NO3 )]·(NO3 ) (M = Cd (1 ), Ni (2 ), Co (3 )), cis -[CoL2 Cl2 ] (C6 H6 ) (4 ), and [Co(L)3 ]·(ClO4 )2 ·(CH3 CN)2 ·(H2 O) (5 ). Abstract: A pyridyl–amine Schiff-base compound (L = N -(2-pyridylmethylene)benzene-1, 4-diamine) reacted with several metal salts (Cd(NO3 )2 ·4(H2 O), Ni(NO3 )2 ·6(H2 O), Co(NO3 )2 ·6(H2 O), CoCl2 ·6(H2 O), Co(ClO4 )2 ·6(H2 O)) to give molecular complexes: [M(L)2 (NO3 )]·(NO3 ) (M = Cd (1 ), Ni (2 ), Co (3 )), cis -[Co(L)2 Cl2 ] (C6 H6 ) (4 ), and [Co(L)3 ]·(ClO4 )2 ·(CH3 CN)2 ·(H2 O) (5 ). Complexes1 –3, whose starting compounds possess NO3 − anions, were isostructural octahedral complexes. In complexes3 –5, whose starting compounds have the same metal but different anions, the anions in the products exhibited different coordination modes depending on the identity of the metal. In all complexes, the amine end of the ligand (L) remains uncoordinated. The thermal behavior of the complexes is also described.